Peliosis Hepatis Simulating Metastatic Liver Disease on FDG PET/CT. (July 2018) - Levin, Daniel; Hod, Nir; Anconina, Reut; Ezroh Kazap, Dina; Shaco-Levy, Ruthy; Lantsberg, Sophie
Abstract : Abstract: A 20-year-old man with gastrointestinal symptoms and weight loss underwent FDG PET/CT, which revealed multiple hypermetabolic hepatic lesions concerning for metastatic liver disease. The outcome of liver biopsy was consistent with the diagnosis of peliosis hepatis which is a rare benign disease characterized by multiple blood-filled cystic spaces in the hepatic parenchyma. The findings of peliosis on FDG PET/CT are not well reported in the literature. These interesting images emphasize the importance of including peliosis hepatis in the differential diagnosis of multiple hypermetabolic hepatic lesions on FDG PET/CT, which could simulate malignancy.